SMED methodology applied to the deep drawing process in the automotive industry - Vieira, A.M. (2020)
The automotive industry has evolved, becoming increasingly demanding. Thus, it becomes necessary to increase the availability of equipment, reacting efficiently to be able to respond to customer requests. Nowadays, the strong development of this industry is based on three main pillars: competitiveness, product quality and response time to requests. The focus of this work is to increase the availability of a deep drawing machine with extremely high setup time, with the main objective of reducing the average setup time by 20%. This reduction is even more important when it comes to the internal setup time, the time the machine is stopped. Thus, the Single-Minute Exchange of Die technique was applied and work standards were improved to reduce the equipment setup time, increasing the machine availability, leading to a production increased output. As a result of this work, it was possible to standardize setup, reducing 38% of total machine setup time, 53% of internal setup time and increasing 7.7% of OEE (Overall Equipment Effectiveness) availability.